2017
DOI: 10.1039/c7nj00819h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and dynamics of a novel proton transfer complex containing 3,5-dimethylpyrazole as a donor and 2,4-dinitro-1-naphthol as an acceptor: crystallographic, UV-visible spectrophotometric, molecular docking and Hirshfeld surface analyses

Abstract: A CT complex is synthesized and characterized by spectral and crystallographic techniques. The Hirshfeld and molecular docking studies are also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Hirshfeld 2‐D finger plots may offer effectual information about interactions between the metal complexes and other atom of the molecular. [ 51,71 ] Figure S2 showed two‐dimensional fingerprint plots generated correspond to the C···H, H···H, and O···H mutual effects arising as particular spikes of complexes 1 and 2 . The H···H connected with verifying to be the greatest proportion with 41.2% and 57.4% of two complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Hirshfeld 2‐D finger plots may offer effectual information about interactions between the metal complexes and other atom of the molecular. [ 51,71 ] Figure S2 showed two‐dimensional fingerprint plots generated correspond to the C···H, H···H, and O···H mutual effects arising as particular spikes of complexes 1 and 2 . The H···H connected with verifying to be the greatest proportion with 41.2% and 57.4% of two complexes.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] This reaction arises from a weak interaction between donors and acceptors. [4][5][6][7][8] Moreover, CT complexes have been used as organic semiconductors 9 and organic solar cells 10 because of their electrical properties. 11,12 It has reported that the solid CT complex is stabilized by two noncovalent interactions, namely, hydrogen bond and dipole-dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary regions were clearly visible in the plots where one molecule acted as an acceptor and the other as a donor. [ 70 ] The extents of H···H interactions were found to be the greatest contribution, which were covered 42.0% and 45.4% of the HS for each molecule of complexes 1 and 2 , respectively. The extents of O···H, C···H and N···H interactions covered 25.4%, 16.3%, and 5.7% of the molecule of complex 1 , respectively.…”
Section: Resultsmentioning
confidence: 99%